2021
DOI: 10.3354/meps13802
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic variation in response to extreme events may facilitate kelp adaptation under future climates

Abstract: Marine heatwaves (MHWs) have caused declines in many kelp forests globally. Although the ecological effects of these climatic extremes have been well examined, studies on the role of genotypic variation in underpinning population responses under pressures are lacking. Understanding how kelps respond to different warming profiles and, in particular, intraspecific variation in responses is necessary to confidently anticipate the future of kelp forests, yet this remains a critical knowledge gap for most species. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 74 publications
1
20
0
Order By: Relevance
“…Gametophytes of Ecklonia radiata used in this experiment came from gametophyte stock cultures kept at the Indian Ocean Marine Research Centre, Crawley, Western Australia (31°58'52.0" S 115°48'57.7" E) under controlled red light and temperature conditions, as described in Alsuwaiyan et al (2021). Stock cultures were originally established from sporophytes haphazardly collected from 11 m depth by SCUBA divers from Hamelin Bay, Western Australia (34°15'22.07" S, 115°0'33.48" E) in April 2019.…”
Section: Experimental Designmentioning
confidence: 99%
“…Gametophytes of Ecklonia radiata used in this experiment came from gametophyte stock cultures kept at the Indian Ocean Marine Research Centre, Crawley, Western Australia (31°58'52.0" S 115°48'57.7" E) under controlled red light and temperature conditions, as described in Alsuwaiyan et al (2021). Stock cultures were originally established from sporophytes haphazardly collected from 11 m depth by SCUBA divers from Hamelin Bay, Western Australia (34°15'22.07" S, 115°0'33.48" E) in April 2019.…”
Section: Experimental Designmentioning
confidence: 99%
“…These results align with previous findings that increased temperature on bull kelp and have found that increased temperatures result in reduced germination rates (Schiltroth 2021), decreased spore settlement, and reduced gametophyte growth (Lind and Konar 2017; Muth et al 2019). Increased temperatures also result in decreased gametophyte survival and sporophyte recruitment in numerous other kelp species including giant kelp ( Macrocystis pyrifera) (Hollarsmith et al 2020), stalked kelp ( Pterygophora californica ) (Howard 2014), spiny kelp ( Ecklonia radiat a) (Alsuwaiyan 2021), sugar kelp ( Saccharina latissima ), and dragon kelp ( Eualaria fistulosa ) (Lind and Konar 2017).…”
Section: Discussionmentioning
confidence: 99%
“…There is great potential to target resilient donor plants, increase their quantity with commercial cultivation, and then propagate strong genotypes on seeded substrates spread onto degraded reefs to increase resilience of seaweed forests to climate change and other threats (Alsuwaiyan et al. 2021, Wood et al. 2021).…”
Section: Figmentioning
confidence: 99%